RESEARCH MAPPING OF MARITIME NAVIGATIONAL TECHNOLOGY BASED ON VISUALIZATION MAPPING APPROACH - Muhammad Sapril Siregar; Rizqiya Windy Saputra; Dedi Kurniawan; Romulo Edison (Jurnal Maritim Malahayati, 2022)
Indonesia is a large country with many spreading archipelagos and many ocean resources. The condition makes Indonesia a potential country in many maritime sectors. The potential condition establish maritime navigational technology is one of many topic that has begun to interest many researches. The strong desire of researcher will also get support from the many sources of citations that are now appearing and can be used as references. Even though it has a wide area of expertise, the researches concerning maritime technology is very little at present. This research aims to collect the trends of maritime technology research in Indonesia by performing bibliometric analysis from scientific papers indexed by partly free scholarly database named google scholar. This research analyzes the numbers of document published, the most cited papers, and the productivity of maritime researchers in two specific area of maritime navigation and maritime navigational technology. Some keywords focused on this researched were minned by clustering using VOSviewer. As the result, this study hopefully provide an overview of current research on maritime technology in Indonesia and provide the right direction for researchers with maritime technology research interest.